Pemetaan Batimetri Alur Pelayaran Perahu Nelayan Sungai Tengket, Arosbaya, Bangkalan - Ahmad Fahmi Wahyudi; Agus Romadhon; Inayatul Lailiyah; Ilham Cahya (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2023)
Arosbaya is one of Madura's coastal areas on the north side of Madura Island. The Arosbaya River is a shipping channel for fishermen in the area to access the sea. To increase coastal potential, data on the depth of shipping lanes on the Arosbaya River is needed to ensure the safety of fishermen. Data on the depth of the shipping channel on the Arosbaya River was obtained from the results of a bathymetric survey. The aim of this research is to analyze the bathymetric conditions of the Arosbaya River waters and provide alternative solutions to the silting that occurs in fishing boat shipping lanes. A bathymetric survey was carried out on the Arosbaya River to the mouth of the Arosbaya River using a Garmin GPSMAP 585 sounding tool. Tidal data was obtained from secondary data and processed using the admiralty method to obtain the harmonic constant. It is known from the formzahl value obtained that f > 3 which means high and low tides. single daily type (diurnal tide). The water level height values ​​obtained were the highest high water level (HHWL) = 1.14 M, mean sea level (MSL) = 0 M, lowest low water level (LLWL) = -1.14 M which was used as a correction in the bathymetric sounding results for making shipping lanes. Soundings were carried out in the survey area with the deepest depth found, namely 2.6 meters which has been corrected for the lowest astronomical tide (LAT). Measurements on 2 types of fishing boat draft, namely curved and boat types, showed that the average draft height was 90-100 cm and 50 cm when the boat was empty without cargo in the water. Both types of fishing boats are included in boats measuring < 5 GT. The depth that the boat can traverse when empty is 50 cm, which makes the channel area smaller because it conforms to an appropriate and safe contour depth (≥ 50 cm). Based on the corrected bathymetry map, the area east of the river has a suitable depth and is safe to pass. The depth of the water at the lowest ebb has the potential to disrupt ship traffic because the area that is safe to pass through is reduced so that it is possible that traffic at the mouth of the river cannot move simultaneously to get in and out of fishing boats.es